2014
DOI: 10.1002/wcm.2552
|View full text |Cite
|
Sign up to set email alerts
|

A gradient‐based multiple‐path routing protocol for low duty‐cycled wireless sensor networks

Abstract: Routing in a low duty-cycled wireless sensor network (WSN) has attracted much attention recently because of the challenge that low duty-cycled sleep scheduling brings to the design of efficient distributed routing protocols for such networks. In a low duty-cycled WSN, a big problem is how to design an efficient distributed routing protocol, which uses only local network state information while achieving low end-to-end (E2E) packet delivery delay and also high packet delivery efficiency. In this paper, we study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…To meet the different requirements of applications, optimizing data flow-based routing algorithms provides efficient solutions, which are classified into two categories based on the number of paths from the source node to the destination node. One is single path-based routing algorithms [59,60], and the other is multi-path-based routing algorithms [61,62].…”
Section: Optimizing Data Flow-based Routing Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…To meet the different requirements of applications, optimizing data flow-based routing algorithms provides efficient solutions, which are classified into two categories based on the number of paths from the source node to the destination node. One is single path-based routing algorithms [59,60], and the other is multi-path-based routing algorithms [61,62].…”
Section: Optimizing Data Flow-based Routing Algorithmsmentioning
confidence: 99%
“…To construct multiple path segments according to the gradient information of nodes, the gradient-based multi-path routing protocol (GMRP) is proposed [61]. The node chooses the path segment that can forward packets to the sink fastest as its next path segment.…”
Section: Multi-path-based Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…FSG establishes safe routes for data transmission by aiding the BS to translate the complete hop information into gradient data. Migabo et al in [41] [42] suggested the GMPR (Gradient-based multipath routing protocol), which is targeted at reinforcing decreased node failures and improved transmission performances through duty-cycling. It applies the sensory reports to gauge the distances of neighboring nodes.…”
Section: Query-driven Routing Solutionsmentioning
confidence: 99%
“…In addition, since some application of EH-WSNs depending on a synchronized notion of time, as a traditional problem of WSNs and EH-WSNs, time synchronization is researched widely for achieving global or local time synchronized; e.g., RBS [34], TPSN [35], and SATS [20]. Other examples can be found in [36], [37], and references therein. Even though numbers approaches have been proposed for EH-WSNs, a single communication technology is utilized in these works for solving the problems of routing protocol and time synchronization.…”
Section: Related Workmentioning
confidence: 99%